Use of Regional Languages in Indonesian Language Learning at Kampar Regency Elementary Schools - Muhammad Amin (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2024)
This research aims to analyze the use of regional languages ​​in student communication in Indonesian language learning at Kampar Regency Elementary Schools. The research method used is field research with a qualitative research method approach and descriptive data analysis. Data collection was carried out by interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, and drawing conclusions/verification. The results of the research are that the use of regional languages ​​in Indonesian language learning in Kampar Regency elementary schools has great potential to improve students' language understanding and skills. The integration of regional languages ​​helps explain complex concepts and enriches the learning process. However, it is important to balance the use of regional languages ​​and Indonesian so that both are supported. With the support of teacher training, development of teaching materials, and community involvement, the use of regional languages ​​can be an effective strategy for improving the quality of education in Kampar Regency.